Analysis of The Effect of Product, Price, Place, and Promotion on Spectator Loyalty of The Surabaya Football Kicking League - Muhammad Aldiansyah (International Journal of Social, Economic, and Business, 2025)
This study aims to analyze the influence of Product (Event Experience), Price (Ticket Price & Participation Fee), Place (Location & Accessibility), and Promotion (Promotion & Digital Marketing) on Participant Loyalty in the 2025 Liga Tendang Bola Surabaya (LTB Surabaya 25). With the global sports industry projected to contribute $599.9 billion to global GDP by 2025, the importance of organizing effective local sports events has increased. This research employs a quantitative approach using multiple linear regression analysis, based on data collected from 370 Gen Z respondents who attended LTB Surabaya 25. The results indicate that all four variables have a positive and significant effect on participant loyalty, both partially and simultaneously. These findings are expected to serve as a basis for developing business strategies in local sports events to enhance participant loyalty and ensure the sustainability of future events.